SWOT ANALYSIS OF ENGLISH COURSE IMPLEMENTATION BY THE BORNEO ENGLISH COURSE (BEC) - Ludwiqa, Chrizzya; Sriwahyuni, Riza; Pratama, Yogi Atma; Afdalia, Tiara; Zaini, Muhammad; Perkasa, Ikhlas Abdi; Paulina, Novely Esterika; Aisyah, Risfa Nur; Altalarik, Agel; Misrita, Misrita (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2022)
Most parents get overwhelmed in guiding their children's learning progress at home because not all come from educational backgrounds. Some parents are also busy at work and don't have enough time to teach their children intensively, so their children's education during this pandemic is not going as well as it should. This study is aim to investigate and to dig deeper into each of the strengths, weaknesses, opportunities and challenges faced to improve and develop learning strategies with SWOT analysis. This study was a qualitative content analysis approach. Content analysis is a qualitative research technique that emphasize the constancy of communication content, the meaning of communication content, the reading of symbols and the meaning of symbolic interactions that occur in communication (Bungin, 2011). The information collected was then analyzed and described in prose. The steps taken were: data collection, SWOT analysis (determining strengths, weaknesses, opportunities and threats), and finding development or improvement strategies. The result showed by changing the recruitment process through the placement test process, adding program variations, and most importantly, creating teaching materials developed by themselves so that the curriculum in the course can run clearly and systematically and the seriousness of the institution in preparing the learning process can be felt by consumers.